Atividades educacionais empregando realidade aumentada mobile para o ensino de força e movimento - Lima, Wilson Vanucci Costa (2020)
This research was developed through an extension project of the Federal University of Santa Maria, which is integrated by Prof. Dr. Cesar de Oliveira Lobo. To carry out the work, there was an intervention at the State School of Basic Education Dom Antônio Reis de Faxinal do Soturnos – RS, through educational activities implemented by the researcher totaling 14 class hours between March and April 2019. The intervention was carried out in two classes of first grade of high school, totaling 38 students. This work proposes to carry out educational activities exploring new possibilities for teaching strength and movement in Basic Education, with the use of technological resources. The present research is of an exploratory qualitative character, of the case study type and was organized based on subsidies explored in a Systematic Review of Literature and in the theory presented by Vygotsky, applied to the teaching area. In this way, it is intended to provide means for students, through social interactions guided by the teacher, to have the possibility of capturing and sharing meanings of physical concepts accepted by the academic and scientific community. This work can serve as a reference of activities for implementation in the classroom, relating the theory of strength and movement, with the realization of educational activities using Digital Technologies of Information and Communication (TDIC), for example, the use of Augmented Reality Mobile (RAM). The greatest difficulty evidenced in the research regarding operability and accessibility when using RAM technology is linked to limited access to the internet to explore the different functionalities of educational media. Through the analysis of the results of questionnaires, class reports and raw materials of the applied educational activities, it was obtained indications that the educational activities carried out can contribute to a potential learning.